Background: Sunlight is useful in the formation of provitamin D, which is useful for increasing the body's immunity. But besides these benefits, there are also negative effects of excess sun exposure, one of which can cause skin cancer. This incident can - Alyandini Saraswati Winata; Reni Angeline; Deviana Deviana; Shintia Christina (Jurnal MedScientiae, 2023)
Sunlight is useful in the formation of provitamin D, which is useful for increasing the body's immunity. But besides these benefits, there are also negative effects of excess sun exposure, one of which can cause skin cancer. This incident can be prevented by using sunscreen regularly and correctly. However, it was found that only a third of adults use sunscreen every day. Therefore, this study was conducted to determine the relationship between knowledge and attitudes toward the behavior of Ukrida Faculty of Medicine students when using sunscreen to prevent skin cancer. The method used in this research uses descriptive-analytic research with a cross-sectional approach. The population used in this study were Ukrida Faculty of Medicine students in 2019, totaling 155 people. With a total sample of 123 respondents who met the inclusion and exclusion criteria. Data collection was done using a questionnaire. The results of this study indicate that there is a relationship between knowledge of behavior with a value of p = 0.027 (< 0.05) and a relationship between attitudes towards behavior with a value of p = 0.000 (< 0.05). Based on the results of the study, it was concluded that there was a significant relationship between knowledge and attitudes toward the behavior of 2019 Ukrida Faculty of Medicine students in using sunscreen to prevent skin cancer. However, most of the respondents did not reapply sunscreen every 2 hours.